2019
DOI: 10.21873/invivo.11553
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Synthetic Polymer-coated Peripherally Inserted Central Catheter in Patients With Advanced Cancer

Abstract: Background/Aim: A peripherally inserted central catheter (PICC) is recommended for the safe administration of anticancer agents. The effectiveness of synthetic polymercoated and non-coated PICCs was compared. Patients and Methods: Patients with advanced cancers who had indwelling PICCs were reviewed using their medical records. Three types of PICCs were compared in terms of complications and catheter failure. Results: A total of 90 patients were retrospectively analyzed, including 31 with Groshong PICCs, 30 wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 10 publications
(13 reference statements)
0
1
0
Order By: Relevance
“…A systematic review 17 suggested that antimicrobial PICCs may reduce CLABSI for the high‐risk population. Takezawa et al 26 showed that synthetic polymer‐coated PICC is safe and has less catheter complications. However, a prospective cohort study involving 52 hospitals showed that antimicrobial and antithrombogenic PICCs cannot reduce catheter complications, and proposed more attention to balance benefits against cost 16 .…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review 17 suggested that antimicrobial PICCs may reduce CLABSI for the high‐risk population. Takezawa et al 26 showed that synthetic polymer‐coated PICC is safe and has less catheter complications. However, a prospective cohort study involving 52 hospitals showed that antimicrobial and antithrombogenic PICCs cannot reduce catheter complications, and proposed more attention to balance benefits against cost 16 .…”
Section: Discussionmentioning
confidence: 99%